The Validity of Quantifying Pulmonary Contusion Extent by Lung Ultrasound Score for Predicting ARDS in Blunt Thoracic Trauma - Mohamed Soliman Sayed; Kareem Abdelhamid Elmeslmany; Ahmed Samir Elsawy; Nashwa Abed Mohamed (Critical Care Research and Practice)
Background. Thoracic trauma comprises 20–25% of all traumas worldwide and constitutes the third most common cause of death after abdominal injury and head trauma in polytrauma patients. Pulmonary contusion (PC) is a common injury seen after blunt trauma that is associated with significant morbidity and mortality. The aim of this prospective study was to determine the value of PC extent measurements using lung ultrasound in predicting high risk patients for ARDS development. Methods. In one year, 50 polytrauma patients with blunt chest trauma were admitted to the ICU at Damanhur Institute. Lung contusion extent was evaluated using a lung US score (LUS) and was compared to the CT contusion score. The ability of the LUS to predict ARDS was tested. The diagnostic accuracy of LUS was compared with chest radiography for lung contusion and pneumothorax with thoracic CT scan as a reference. Patients were restratified by LUS into two groups: severe and nonsevere contusion group. The two groups' data were compared with respect to difference in mortality and injury characteristics. Results. Lung contusion assessed by LUS score was well correlated to thoracic CT scan measurements (r = 0.78). A LUS of 4 was defined as a cut-off value for predicting ARDS development within 72 hours of trauma with sensitivity and specificity (91.67% and 84.21%), respectively. Patients with severe lung contusions had a lower hypoxic index on admission, more ventilator days, a higher risk of ARDS development, more fractured ribs; higher rate of hemothorax and a higher ISS score than patients with nonsevere lung contusions. Conclusion. LUS on admission can quantify lung contusion extent and the high risk of developing ARDS after blunt thoracic trauma.